Strategi Public Relations Melalui Konten Instagram Untuk Brand Awareness Di Klinik Gigi (Analisis Deskriptif Di Mirza Ms Dental Care) - Dea Sunarti; Arvin Hardian; Muhamad Khadafi Firman (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
In today's digital era, business competition is getting tighter. Including in the field of dental health. This study aims to determine and analyze Public Relations Strategy by using Instagram social media @mirzams.dentalcare to build Brand Awareness at the Mirza MS Dental Care Dental Clinic. The method used is descriptive qualitative to understand the strategy in depth and comprehensively. with content observation techniques, interviews, and documentation. The main theory used is Brand Awareness with indicators of recognition, recall, top of mind, and brand image, as well as New Media theory as a support. The results of the study show that PR strategy is carried out through collaborative content with KOL/UMKM, entertainment, promotion, and education. Collaborative content strengthens recognition, routine programs build recall, the use of hashtags supports top of mind, while educational and entertainment content forms brand image. PR strategy is implemented through the stages of planning, implementation, and evaluation. Although brand awareness has increased, the level of engagement still needs to be improved compared to competitors.